Development of an automated irrigation system for horticultural nurseries - Zakaria, Abdul Aziz (Universiti Putra Malaysia, 1999)
Horticulture is becoming an important sector in the agricultural industry. Due to increasing demand for planting materials, horticultural nurseries are being established in many parts of the country. Irrigation is one of the most important operations for any nursery to produce salable plants. With increasing cost of labour and less attractive working environment in the agricultural sector, automation of irrigation and other agricultural practices, is a necessity in order for the horticultural industry to survive. An automated micro-irrigation system is being developed and evaluated at UPM. An imported 6-station controller, solenoid valves, and micro-sprayers were installed to irrigate fruit seedlings grown in ceramic pots. Initial work is on determining plant water requirements for scheduling the system operation. For nurseries with enough pressure from the main, use of battery-operated valves are recommended.